CULTURE SHOCK DALAM PROSES KOMUNIKASI ANTARBUDAYA MAHASISWA PAPUA DI UNIVERSITAS RIAU - Andini, Laras Putri; Yazid, Tantri Puspita (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2024)
Differences in culture act as a trigger for experiencing culture shock among parties involved in intercultural communication. Students from Papua are an example of those who undergo culture shock. This culture shock occurs when Papua students choose to pursue their education at the University of Riau. The aim of this research is to understand culture shock in the process of intercultural communication and the challenges that arise during this adaptation process. Culture shock experienced by Papua students at the University of Riau isn't limited to differences in language and dialect during communication but extends to their social interactions, food preferences, and the different climate experienced after their decision to migrate. This study utilizes a descriptive qualitative approach, gathering primary and secondary data from three student informants. Data collection techniques involve interviews, observations, and documentation. Data analysis methods include data reduction, data presentation, and drawing conclusions. To ensure data validity, source triangulation and temporal triangulation are employed. The research findings reveal varying conditions experienced by each Papua student in the four cultural adaptation phases according to Oberg and Samova. Many factors contribute to the occurrence of culture shock among migrant students, both internal and external. Nonetheless, these students choose to persevere and face the existing conditions, thus overall adapting to the new culture. However, obstacles in the adaptation process for Papua students mainly stem from their surrounding environment.